Molecular cloning, developmental expression and tissue distribution of diapause hormone and pheromone biosynthesis activating neuropeptide in the bamboo borer Omphisa fuscidentalis - Suphawan Suang (2018)
© 2015 The Royal Entomological Society. Diapause, an arrested period of post-embryonic development in insects, is under the control of hormonal interactions. In the bamboo borer Omphisa fuscidentalis Hampson (Lepidoptera: Crambidae), larvae remain in diapause for as long as 9months during the dry season, from September to the following June, although the factors that regulate larval diapause are poorly understood. The present study describes the cloning and expression analysis of the diapause hormone and pheromone biosynthesis activating neuropeptide (DH-PBAN) precursor of O. fuscidentalis (Ompfu-DH-PBAN cDNA), aiming to reveal how it may be involved regulating larval diapause in this species in combination with environmental factors. The open reading frame (ORF) of the cDNA encodes a 199-amino acid precursor protein that contains DH, PBAN and three other neuropeptides, all of which share a conservative C-terminal pentapeptide motif FXPR/KL (X=G, T or S). The Ompfu-DH-PBAN is highly similar (74%) to the DH-PBAN of the legume pod borer (Maruca vitrata). A quantitative real-time polymerase chain reaction reveals that Ompfu-DH-PBAN mRNA is expressed only in neural tissues and that expression is highest in the suboesophageal ganglion. In addition, the expression level of Ompfu-DH-PBAN mRNA in the suboesophageal ganglion is consistently high during the fifth larval instar, increasing moderately in early diapause before reaching a peak during late diapause. After pupation, expression of the Ompfu-DH-PBAN precursor decreases to a low level. In addition to endocrine factors, the results demonstrate that photoperiod increases the expression level of Ompfu-DH-PBAN mRNA in larval diapause. These results also suggest that the expression of the Ompfu-DH-PBAN gene correlates with larval diapause development and may be activated by photoperiod in O. fuscidentalis.